Coadministration of CD19- and CD22-Directed Chimeric Antigen Receptor T-Cell Therapy in Childhood B-Cell Acute Lymphoblastic Leukemia: A Single-Arm, Multicenter, Phase II Trial. Issue 9 (20th March 2023) - Wang, Tianyi; Tang, Yanjing; Cai, Jiaoyang; Wan, Xinyu; Hu, Shaoyan; Lu, Xiaoxi; Xie, Zhiwei; Qiao, Xiaohong; Jiang, Hui; Shao, Jingbo; Yang, Fan; Ren, Hong; et al.
Abstract : PURPOSE: We determined the safety and efficacy of coadministration of CD19- and CD22-chimeric antigen receptor (CAR) T cells in patients with refractory disease or high-risk hematologic or isolated extramedullary relapse of B-acute lymphoblastic leukemia. PATIENTS AND METHODS: This phase II trial enrolled 225 evaluable patients age ≤ 20 years between September 17, 2019, and December 31, 2021. We first conducted a safety run-in stage to determine the recommended dose. After interim analysis of the first 30 patients treated (27 at the recommended dose) showing that the treatment was safe and effective, the study enrolled additional patients according to the study design. RESULTS: Complete remission was achieved in 99.0% of the 194 patients with refractory leukemia or hematologic relapse, all negative for minimal residual disease. Their overall 12-month event-free survival (EFS) was 73.5% (95% CI, 67.3 to 80.3). Relapse occurred in 43 patients (24 with CD19 + /CD22 + relapse, 16 CD19 – /CD22 +, one CD19 – /CD22 –, and two unknown). Consolidative transplantation and persistent B-cell aplasia at 6 months were associated with favorable outcomes. The 12-month EFS was 85.0% (95% CI, 77.2 to 93.6) for the 78 patients treated with transplantation and 69.2% (95% CI, 60.8 to 78.8) for the 116 nontransplanted patients ( P = .03, time-dependent covariate Cox model). All 25 patients with persistent B-cell aplasia at 6 months remained in remission at 12 months. The 12-month EFS for the 20 patients with isolated testicular relapse was 95.0% (95% CI, 85.9 to 100), and for the 10 patients with isolated CNS relapse, it was 68.6% (95% CI, 44.5 to 100). Cytokine release syndrome developed in 198 (88.0%) patients, and CAR T-cell neurotoxicity in 47 (20.9%), resulting in three deaths. CONCLUSION: CD19-/CD22-CAR T-cell therapy achieved relatively durable remission in children with relapsed or refractory B-acute lymphoblastic leukemia, including those with isolated or combined extramedullary relapse.